Anatomical study of the leaves and evaluation of the chemical composition of the volatile oils from Psidium guineense Swartz leaves and fruits (Research, Society and Development, 2021)
Psidium guineense Swartz is a bush used in urinary tract diseases, diarrhea, and dysentery. The present study aims to perform the anatomical study of the leaves and evaluation of the chemical composition of the volatile oils from Psidium guineense Swartz leaves and fruits. The botanical material was collected in Hidrolândia, Goiás. Anatomical characterization and phytochemical screening of the leaves were performed by conventional methods. Leaf and fruit (green fruits, immature fruits, and ripe fruits) powders were submitted to hydrodistillation in the Clevenger apparatus and the identification of the chemical components of the volatile oils obtained was done by GC-MS. The leaf blade is hypoestomatic with paracytic and anisocytic stomata. Secretory cavities are observed in the central vein, mesophyll, petiole, and young stem. The powder moisture content was 7.4%. The total ash content of the leaf powder was 6.3% and the acid-insoluble ash content was 0.8%. The presence of tannins, flavonoids, and saponins in the leaves were identified. Leaves volatile oil’s majority compounds were 2Z,6E-farnesol (23.1-25.4%), α-copaene (17.7-20.3%), muurola-4,10(1.4) dien-1-β-ol (5.8-6.7%), epi-α-cadinol (5.5- 6.3%), and δ-Cadinene (5.0- 5.9%). Fruits volatile oil’s majority compounds were 2Z,6E-farnesol (31.9-41.4%), α-copaene (13.3-26.6%), δ-cadinene (5.4-9.8%), γ-himachalene (3.8-6.1%), and cubenol (2.6-6.1%). This is the first report on anatomical study of the leaves, and chemical composition of volatile oils from leaves and fruits of P. guineense collected in Hidrolândia, Goiás.